2016
DOI: 10.1212/nxi.0000000000000286
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient treatment of severe depression in neuromyelitis optica spectrum disorder

Abstract: Objective:To investigate depression frequency, severity, current treatment, and interactions with somatic symptoms among patients with neuromyelitis optica spectrum disorder (NMOSD).Methods:In this dual-center observational study, we included 71 patients diagnosed with NMOSD according to the International Panel for NMO Diagnosis 2015 criteria. The Beck Depression Inventory (BDI) was classified into severe, moderate, or minimal/no depressive state category. We used the Fatigue Severity Scale to evaluate fatigue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 42 publications
3
69
1
4
Order By: Relevance
“…In NMOSD and MS, fatigue has been reported to impair activities of the daily living [6,[8][9][10]. In MS patients, the prevalence of fatigue was reported to be 50% to 90%, and more than 20 trials were performed to determine the appropriate treatment for fatigue [6,11]. Another study showed 36.5% of early MS patients exhibited fatigue [12].…”
Section: Introductionmentioning
confidence: 99%
“…In NMOSD and MS, fatigue has been reported to impair activities of the daily living [6,[8][9][10]. In MS patients, the prevalence of fatigue was reported to be 50% to 90%, and more than 20 trials were performed to determine the appropriate treatment for fatigue [6,11]. Another study showed 36.5% of early MS patients exhibited fatigue [12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, certain lesions that were considered to be neurologically asymptomatic may in fact cause subtle neurologic manifestations that could be masked by more prominent symptoms in the context of an attack of ON or myelitis. A recent study reported that 28% of patients with NMOSD suffered from unrecognized and untreated depression which was also associated with neuropathic pain and fatigue [13]. The unrecognized depression and fatigue in NMOSD patients could also make us overlook subtle symptoms from brain lesions at least in some of our patients.…”
Section: Discussionmentioning
confidence: 93%
“…1 A study in 2016 has demonstrated that depression in NMOSD patients is linked to neuropathic pain and fatigue if these conditions are poorly treated. 10 Better knowledge regarding the mechanisms of pain in NMOSD patients is urgently needed in order to expand existing knowledge, which in the long run could be beneficial for this group of patients. 7…”
Section: Neuromyelitis Optica Spectrum Disordermentioning
confidence: 99%